The impact of Political Events and Covid-19 pandemic on Return Volatilities of 3 Sectors in the Stock Exchange of Thailand during 2019 to 2021 - Dumdoung, Samitanan; Witsaroot Pariyaprasert; Nawaporn Vimolphattanatham (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The objective of this paper is to study the impact of political events and Covid-19 pandemic on return volatilities of the sectorial stock market in Thailand. The researcher specifically used ARMA model for main equation and one EGARCH model for the volatility equation. This model is applied to the daily returns relevant to three selected sector indexes of stock exchange of Thailand from 25 March 2019 to 24 March 2021. To test the effect of political events and Covid-19 on banking sectors, consumer product sectors, and service sectors indexes stock market return volatility. The results show that both political events and Covid-19 pandemic have significantly affected on return volatility of the selected sector indexes. However, the return volatilities of Service sector are not affected by Covid-19 pandemic. Results show that political events and Covid-19 pandemic significant effect on return volatility of Bank sector index continuously 3 days of the delay effects of the situations. In addition, violent protest and Thai general election have positive impact on return volatility. It refers that the stock was more volatized. The volatility of the sectorial index of consumer product was affected by Covid-19 pandemic. In part of political events, student’s protest has affected continuously 3 days. And other political events have significant effect on second and third day after the situation. Meanwhile, all of situations have negative impact, except student’s protest. Furthermore, results confirm that main three political events and Covid-19 pandemic have stronger effect on return volatility of selected sector index stock market in Thailand.